Myanmar Military Coup: Can ICCPR Protect Civil Society? - Pasha, Vanhar Camal; Novianti, Novianti; Harahap, Rahayu Repindowaty (Faculty of Law, Universitas Jambi, 2024)
This study aims to find out how the International Convention On Civil And Political Right protects Myanmar Civil Society in the Myanmar Military Coup Case and how the legal protection for Myanmar civil society against conflicts that occur in the region. This research is a normative legal research. With a statute approach, case approach and conceptual approach. Based on research, that in the convention on civil and political rights there are provisions that regulate and guarantee the rights of civil society, but the rights of civil society in Myanmar are not guaranteed due to the coup conflict and the struggle for power in the country. This shows that the convention on civil and political rights has not optimally guaranteed the protection of the rights of civil society. As well as how ASEAN's role in resolving conflicts carried out by the Myanmar military against Myanmar's civil society. The forms of protection of Myanmar's civil society are contained in the existing rule of law and if there is a problem, this problem is resolved at the Summit or ASEAN Summit level